A Foreign Body Through the Shoe of a Person With Diabetic Peripheral Neuropathy Alters Contralateral Biomechanics: Captured Through Innovative Plantar Pressure Technology. (June 2018) - Chatwin, Katie E.; Abbott, Caroline A.; Reddy, Prabhav N.; Bowling, Frank L.; Boulton, Andrew J. M.; Reeves, Neil D.
High plantar pressure as a result of diabetic peripheral neuropathy is often reported as a major risk factor for ulceration. However, previous studies are confined to laboratories with equipment limited by cables, reducing the validity of measurements to daily life. The participant concerned in this case report was wearing an innovative plantar pressure feedback system as part of a wider study. The system allows for continuous plantar pressure monitoring and provides feedback throughout all activities of daily living. The participant concerned was a 59-year-old male with type 2 diabetes who presented with severe peripheral neuropathy. In addition, the right ankle had previously undergone fusion. Between monthly study appointments, the participant unknowingly had a screw embedded in his right shoe, while pressure was being recorded. Although no significant differences in pressure were present for the right foot with the embedded screw, the contralateral foot showed significantly higher pressure when the screw was embedded, compared with pre and post time periods. The increase in pressure on the contralateral foot is expected to result from the protrusion of the screw in the right shoe, causing a perturbation to balance and a shift in the center of pressure toward the contralateral side. This compensatory effect is likely to have been magnified by the limited mobility of the fused right ankle. These findings highlight the importance of checking both feet for ulcer risk, in the event of receiving high-pressure feedback. This innovative technology may improve our understanding of diabetic plantar foot ulcer development.